LO68: Does point-of-care ultrasonography change actual care delivered by shock subcategory in emergency department patients with undifferentiated hypotension? An international randomized controlled trial from the SHoC-ED investigators. (May 2019) - Atkinson, P.; Hunter, S.; Peach, M.; Taylor, L.; Kanji, A.; Lewis, D.; Milne, J.; Diegelmann, L.; Lamprecht, H.; Stander, M.; Lussier, D.; Pham, C.; et al.
Abstract : Introduction : Although use of point of care ultrasound (PoCUS) protocols for patients with undifferentiated hypotension in the Emergency Department (ED) is widespread, our previously reported SHoC-ED study showed no clear survival or length of stay benefit for patients assessed with PoCUS. In this analysis, we examine if the use of PoCUS changed fluid administration and rates of other emergency interventions between patients with different shock types. The primary comparison was between cardiogenic and non-cardiogenic shock types.Methods : A post-hoc analysis was completed on the database from an RCT of 273 patients who presented to the ED with undifferentiated hypotension (SBP <100 or shock index > 1) and who had been randomized to receive standard care with or without PoCUS in 6 centres in Canada and South Africa. PoCUS-trained physicians performed scans after initial assessment. Shock categories and diagnoses recorded at 60 minutes after ED presentation, were used to allocate patients into subcategories of shock for analysis of treatment. We analyzed actual care delivered including initial IV fluid bolus volumes (mL), rates of inotrope use and major procedures. Standard statistical tests were employed. Sample size was powered at 0.80 (α:0.05) for a moderate difference.Results : Although there were expected differences in the mean fluid bolus volume between patients with non-cardiogenic and cardiogenic shock, there was no difference in fluid bolus volume between the control and PoCUS groups (non-cardiogenic control 1878 mL (95% CI 1550 – 2206 mL) vs. non-cardiogenic PoCUS 1687 mL (1458 – 1916 mL); and cardiogenic control 768 mL (194 – 1341 mL) vs. cardiogenic PoCUS 981 mL (341 – 1620 mL). Likewise there were no differences in rates of inotrope administration, or major procedures for any of the subcategories of shock between the control group and PoCUS group patients. The most common subcategory of shock was distributive.Conclusion : Despite differences in care delivered by subcategory of shock, we did not find any significant difference in actual care delivered between patients who were examined using PoCUS and those who were not. This may help to explain the previously reported lack of outcome difference between groups.